Patient satisfaction with the quality of dental treatment provided by interns - Kun-Tsung Lee; Chun-Ming Chen; Shun-Te Huang; Yi-Min Wu; Huey-Er Lee; Kun-Jung Hsu; Han-Sheng Chen; Ju-Hui Wu (Elsevier, 2013)
Background/purpose: Although proper training of medical and dental interns is particularly important, there are no studies to date in Taiwan examining the quality of dental services provided to the public by interns. The purpose of study is to investigate the significant factors that influence the patient's satisfaction with the quality of dental treatment provided by Interns. Materials and methods: This study randomly selected patients from a dental department in a medical center located in southern Taiwan and used a structured questionnaire and response scales (Likert) to investigate the level of emphasis and satisfaction of patients with the dental treatment provided by interns in February to April 2004 (52 total valid questionnaires). Results: With regard to technical competence compared to that of dentists, we found statistically significant differences according to the type of treatment received, gender, marital status, educational level attained, and household income (P < 0.05). Conclusion: Medical centers should guide interns in clinical cases and provide structured training. These measures could enhance the public's confidence in interns and improve patient satisfaction with interns through improved clinical skills, and provide an excellent work force for the dental field.